Kajian Yuridis Perkembangan Hukum Perbankan Dan Implikasinya Terhadap Pembaruan Hukum Perdata - Oktaviana Maharani; Meilan Arsanti (PMIH Untag Semarang, 2023)
The increasingly rapid development of technology will later replace traditional procedures, and standard agreements used by banks or other financial sectors in utilizing information technology in the development of banking practices, this utilization is in the form of digital banking. This has implications for the development of transactions and banking transaction objects, which adapt many types of transactions and transaction objects from the common law system. The approach method used in this study is normative juridical, analyzed qualitatively and analytically descriptive in nature. The results of this study are the contribution made by the development of transactions and object transactions that have a positive impact on the development of civil law in Indonesia, in particular, Book 2 and also Book 3 of the Civil Code.